SUSTAINABILITY REPORTS COMPARISON BETWEEN PT HOLCIM INDONESIA TBK AND PT INDOCEMENT TUNGGAL PRAKASA TBK - Firstadea, Evanti (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research are aimed to understand the sustainability reports of PT Holcim Indonesia Tbk and PT Indocement Tunggal Prakasa Tbk, and to determine whether they are in accordance with GRI G3.1. The researcher also compared the sustainability report of those companies to know which one is more in accordance with GRI G3.1. This research applied Qualitative Comparative Analysis (QCA) to interprete the content of sustainability reports of the companies.   This analysis focused on  the six indicators, namely  Economic indicator (EC), Environmental indicator (EN), Labor Practices and Decent Work indicator (LA), Human Rights indicator (HR), Society indicator (SO), and Product Responsibility indicator (PR).  The data collection techniques used  in this research are the documentation and literature study.  By comparing sustainability reports issued by the companies toward the guidelines issued by GRI, it is found that PT Holcim Indonesia Tbk has fully fulfilled 24% core indicators and 28% additional indicators, and the company has  also partially fulfilled 76% core indicators and 72% additional indicators. Meanwhile, PT Indocement Tunggal Prakasa Tbk has fully fulfilled 38% core indicators and 43% additional indicators, and the company has also partially fulfilled 62% core indicators and 57% additional indicators. From the results compared to the application level requirement, it shows that PT Holcim Indonesia Tbk achieves grade C while PT Indocement Tunggal Prakasa Tbk achieves grade B. This research confirms that the sustainability report of PT Indocement Tunggal Prakasa Tbk is more in accordance with GRI G3.1 guidelines than PT Holcim Indonesia Tbk. Key words:  Sustainability report, GRI, PT Holcim Indonesia Tbk, PT      Indocement Tunggal Prakasa Tbk